Identification of mRNA expression biomarkers associated with epilepsy and response to valproate with co-expression analysis - Min, Jun; Chen, Qinglan; Wu, Wenyue; Zhao, Jing; Luo, Xinming (Frontiers in Neurology, 2022)
Purpose Valproate (VPA) resistance was reported to be an important predictor of intractable epilepsy. We conducted this study to identify candidate biomarkers in peripheral blood correlated with VPA resistance. Methods The microarray dataset (GSE143272) was downloaded from the Gene Expression Omnibus database. Weighted gene co-expression network analysis (WGCNA) was performed to construct co-expression modules and obtain the most prominent module associated with VPA resistance. Differentially expressed genes (DEGs) between VPA-responsive and VPA-resistant patients were obtained using the “Limma” package in R. The intersections between the most prominent module and DEGs were identified as target genes. Metascape was performed to discover the possible involved pathways of the target genes. GeneCards database was used to know the function of each target gene. Results All genes in the GSE143272 were divided into 24 different modules. Among these modules, the darkred module showed a pivotal correlation with VPA resistance. A total of 70 DEGs between VPA-responsive and VPA-resistant patients were identified. After taking the intersection, 25 target genes were obtained. The 25 target genes were significantly enriched in T cell receptor recognition, T cell receptor signaling pathway, regulation of T cell activation, cytokine–cytokine receptor interaction, and in utero embryonic development. Half of the target genes (CD3D, CD3G, CXCR3, CXCR6, GATA3, GZMK, IL7R, LIME1, SIRPG, THEMIS, TRAT1, and ZNF683) were directly involved in the T cell development, migration, and activation signaling pathway. Conclusion We identified 25 target genes prominently associated with VPA resistance, which could be potential candidate biomarkers for epilepsy resistance in peripheral blood. The peripheral blood T cells may play a crucial role in VPA resistance. Those genes and pathways might become therapeutic targets with clinical usefulness in the future.